(untitled) (Research, Society and Development, 2022)
Idiopathic Thrombocytopenic Purpura is characterized by a decrease in the number of circulating platelets, considered autoimmune and benign, and can be classified according to the diagnosis, age and duration of the disease. The objective was to review the scientific literature on the occurrence of idiopathic thrombocotopenic purpura in children and possible nursing interventions. This is a qualitative exploratory narrative review study carried out in different electronic databases. It was analyzed that research on the disease exists controversial issues about the diagnosis, treatment and adequate follow-up for patients with the pathology. In this way, it is necessary that more studies are carried out in greater depth on the subject, thinking about the treatment and increasing the life expectancy of patients with this disease.